Dynamics Modeling and Simulation of Rolling Shear Mechanism with PR-11RⅢ Composite Connecting Rod - Zhang Duo; Huang Qingxue; Chu Zhibing; Wei Dong (Jixie chuandong)
A new rolling shear mechanism which is driven by one horizontally positioned hydraulic cylinder is put forward through analyzing the present shear mechanism at home and abroad. In order to achieve pure rolling and shearing,the simplify model of PR-11RⅢ-level composite rod linkage mechanism is obtained.Besides,by using the method of assur-group decomposition modeling,the dynamics model of every assur-group and corresponding simulation model are established,and the simulation module of the corresponding function is compiled. Finally,depending on the development project on extensive popularization of 2 000 mm rolling shear mechanism driven by one hydraulic cylinder of a machinery company,the dynamics simulation is conducted by using the Matlab/Simulink. The important basis for mechanism design of the rolling shear and control principle analysis and actual use is provided by the dynamics curve and parameter of key hinge joint botained from the simulation result,the correctness of the dynamic analysis is verified.